Vliv stavebních investic do infrastruktury cestovního ruchu na rozvoj regionů - Fojtů, Jakub (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Bakalářská práce se zabývá problematikou regionální politiky EU ve vazbě na regionální rozvoj. Hlavní tématem bakalářské práce jsou veřejné stavební investice realizované do cestovního ruchu pomocí regionálních operačních programů z programového období 2007 - 2013. Cílem práce je zjistit, zda dochází k naplnění původních intervencí při schvalování těchto investic a zda prostřednictvím těchto investic dochází k rozvoji regionu.

The bachelor's thesis deals with the issue of EU regional policy in relation to regional development. The main topic of the bachelor's thesis is public construction investments implemented in tourism with the help of regional operational programs from the program period 2007 - 2013. The aim of the bachelor's thesis is to find out whether the original interventions during the approval of these investments are being fulfilled and whether the development of the region is taking place through these investments.
The influence of construction investments in tourism infrastructure on the development of regions
Keywords: Evropská unie; regionální politika; regionální operační program; strukturální a investiční fondy; projektový cyklus; programové období; cestovní ruch; region; mikroregion; indikátory; dotace; hrubý domácí produkt; hrubý národní produkt; European Union; regional policy; regional operational program; structural and investment funds; project cycle; program period; tourism; region; microregion; indicators; subsidies; gross domestic product; gross national product.